Meningkatkan Pembangunan Fisik Desa Berdasarkan Efektivitas Pengelolaan Dana Desa - Infonerus Dwi Nugroho; Yuwita Ariessa Pravasanti; Desy Nur Pratiwi (Nur Science Institute, 2022)
This research aims to determine the effectiveness of village fund management on physical development in Sukorejo Village, Wonosari District, Klaten Regency in 2021. The research population is village officials and all residents of Sukorejo Village. The sampling technique used purposive sampling technique with the first sample from the village apparatus which amounted to 3 people consisting of the Village Head, Village Secretary and Village Treasurer, then the second sample from residents totaling 7 people was chosen randomly, so that the results obtained 10 people were used as samples. . Methods of data collection using the interview method. The test results obtained from this study are that in 2021 the management of village fund allocations for village physical development is less effective, due to factors, namely the COVID-19 pandemic and used for direct cash assistance, so that the allocation that should be used for village development instead it was absorbed for direct cash assistance and overcoming the pandemic in Sukorejo Village